ANALISIS STRATEGI DALAM PENGELOLAAN USAHA KOPERASI MAHASISWA DI UNIVERSITAS ISLAM NEGERI RADEN MAS SAID SURAKARTA - pradana, rizqi; Widia Ningrum, Meilin Nur Ningtyas; Muntaha, Faqih Hilmi Muntaha; Ramadhani, Ilham Ramadhani (FEB-UP Press, 2024)
Abstract Student cooperatives are student activity units engaged in business in which there are various activities consisting of various fields that require management or management. Therefore, this article discusses how to manage a business through a student activity unit, namely KOPMA at Raden Mas Said State Islamic University Surakarta. The research method used is qualitative, namely the direct survey method and experiments, because the institution under study is a campus institution or student activity unit. The data source used from this research is conducting interviews with several members and students who are included in the student cooperative institution. then for this research data analysis technique such as through observation, interviews, and direct surveys. The results showed that KOPMA collaborated with several producers and founders in developing its business. KOPMA has various different fields of business, one of which is the most important business in the field of PSDA, because it has a goal of developing member resources and has a connection from one field to another. To hone the skills of members, KOPMA has a work project by holding training seminars in the field of entrepreneurship or the like according to the needs of KOPMA itself. Keywords: Management, Student Cooperatives, and Resources